2017
DOI: 10.1097/prs.0000000000003515
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Hospital Volume, Surgeon Volume, and Surgeon Experience with Complications and 30-Day Rehospitalization after Free Tissue Transfer: A National Population Study

Abstract: Background Greater provider volume is associated with better outcomes. There is, however, a paucity of evidence on volume-outcome associations for surgical complications and 30-day all-cause rehospitalization after free tissue transfer (FTT) or free flap. Surgical complications and frequent rehospitalization are important quality indicators that substantially hinder appropriate healthcare spending. We hypothesized that increased provider volume and surgeon experience are associated with lower complication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…In general, postoperative complications are reported to be associated with hospital volume in several types of disease [9]. Recently, investigations of not only hospital volume, but also surgeon volume, have shed light on surgery for gastrointestinal cancer, emergency surgery and other surgeries [10][11][12][13]. With regard to gastric cancer, Coupland et al recently reported that increasing hospital volume was associated with lower mortality, suggesting that further centralization of esophageal and gastric cancer surgical services was warranted in England [14].…”
Section: Introductionmentioning
confidence: 99%
“…In general, postoperative complications are reported to be associated with hospital volume in several types of disease [9]. Recently, investigations of not only hospital volume, but also surgeon volume, have shed light on surgery for gastrointestinal cancer, emergency surgery and other surgeries [10][11][12][13]. With regard to gastric cancer, Coupland et al recently reported that increasing hospital volume was associated with lower mortality, suggesting that further centralization of esophageal and gastric cancer surgical services was warranted in England [14].…”
Section: Introductionmentioning
confidence: 99%
“…In any operation, increasing volume typically, though not always, improves results and decreases complication rates. [18][19][20] Though one may argue, busier surgeons also have more referrals from other physicians to perform secondary surgery. This has not been specifically addressed for rhinoplasty, however.…”
mentioning
confidence: 99%
“…7 Indeed, Mahmoudi and colleagues showed that the risk of postoperative complications after free flap surgery was lower in high-volume and more experienced surgeons. 8 The well-documented volume-outcome ratio provided further, emphasises the importance of technical skills with evidences supporting lower risk of operative death for patients treated at a high volume center. 9 The lower mortality rate may, however, in part be explained by superior multidisciplinary care at the high volume centere and patient selection.…”
Section: Technical Skillsmentioning
confidence: 92%